Asymptomatic ST-depression during exercise testing in children and adolescents with type 1 diabetes mellitus and autonomic dysfunction - Dmitry Nikitich Laptev; Tamara Leonidovna Kuraeva; Galina Vladimirovna Ryabykina; Sergey Dmitrievich Polyakov; Irina Timofeevna Korneeva; Leila Seymurovna Namazova-Baranova (Сахарный диабет)
Aim. The aim of this study was to investigate cardiac autonomic function as assessed by ST dynamics during and post-exercise in children and adolescents with type 1 diabetes mellitus (T1DM). Materials and methods. The study included 71 young patients with T1DM. The patients were aged 9?18 years and had no history of macrovascular disease or renal disease, including microalbuminuria. Cardiac autonomic function was assessed using cardiovascular tests and 24-h ECG monitoring with automatic calculation of QT interval and heart rate variability parameters. Each patient underwent the physical working capacity 170 test. Results. The prevalence of cardiovascular autonomic neuropathy (CAN) was 30.9%. The frequency of asymptomatic ST-segment depression increased during exercise in 10 (45.5%) patients with CAN (CAN+) compared with 9 (18.4%) patients without CAN (CAN-; p=0.042). During the recovery period, asymptomatic ST-segment depression was present in the first minute in 8 (36.4%) CAN+ patients compared with 1 (2%) CAN- patient (p=0.0003) and in the second minute in 5 (22.7%) CAN+ patients compared with 1 (2%) CAN- patient (p=0.0095). Conclusion. Children and adolescents with T1DM and impaired autonomic function have increased prevalence of asymptomatic ST-segment depression during and post-exercise. The presence of cardiovascular risk factors in children and adolescents with T1DM and CAN may contribute to the increased cardiovascular morbidity and mortality during adulthood in patients with T1DM.